Comparative Analysis of Financial Performance in Indonesian Islamic Banks: The Impact of Spin-Offs, Mergers, and Conversion - Rusmita, Sylva Alif; Salleh, Marhanum Che Mohd; Samad, Khairunnisa Abd (Economica: Jurnal Ekonomi Islam, 2022)
This study conducts a comparative analysis of Indonesian Islamic banks' performance before and after spin-off, merger, and conversion. Using a quantitative approach, the research applies paired t-tests and Wilcoxon tests to assess financial performance across six categories: liquidity, financing, efficiency, profitability, capital adequacy, and non-performing financing. Data from six Islamic banks over ten years were analyzed, comparing performance pre- and post-establishment. The findings reveal no significant differences in performance for banks that underwent pure spin-offs. However, banks formed through mergers demonstrated improvements in operational efficiency, return on assets (ROA), and capital adequacy (CAR), while conversions exhibited strong financing performance but faced capital risk and lower profitability. These results suggest that mergers offer a more efficient establishment method for enhancing bank performance, while conversions require careful capital management. The research highlights the importance of strategic decisions regarding the choice of establishment method for Islamic banks, with significant implications for bankers and policymakers aiming to optimize Islamic bank performance.